Infant formula milk promotion: a multimodal critical discourse analysis of packaging and homepages - Lake, Fiona (2020)
This thesis investigates the discourses evident in infant formula milk promotion in the UK. The data which are analysed comprise packaging of formula preparations for babies and toddlers, and the Internet homepages of infant milk formula manufacturers’ online ‘clubs’ for parents. The study offers a new, interdisciplinary perspective through the application of a multimodal critical discourse analysis approach, drawing on sociological work on nutrition and food promotion. Representations of the child, which are embedded in infant formula promotional texts, are also interrogated; and the textual and visual realisations of an online, commercially motivated club ‘community’ for parents are analysed. The critical stance, in relation to the data and their socio-cultural context, acknowledges that power and ideology are at work in discourses which are communicated by large, profit-driven organisations such as food manufacturers. The study examines how human participants are represented, linguistically and visually, in relation to the promotional texts which are in evidence in the packaging and the ‘club’ homepages. Are some participants and topics excluded or occluded, and how is this strategy put into effect? Furthermore, I question what relationship with the reader/viewer is built, through images and text, and how these positions or social roles are communicated. The study has discovered that a reductive, quantifying discourse of nutrition is communicated on packaging, and that the text and graphic images on the packs can covertly enable health claims to be made. This discourse is less salient in the ‘club’ homepages. However, a form of communication which promotes the manufacturers’ childcare expertise is in evidence in the ‘club’ homepages, alongside representations of parenthood and of a club ‘community’. These representations are limiting and socially exclusive. The study extends existing knowledge about formula promotion used by the large corporate entities and the larger discourses this form of marketing connects with, by applying multimodal analysis underpinned by sociological theorising of branding, health and nutrition. The implications of the findings for parents and carers are presented, and the multimodal communicative aspects of infant milk promotion which escape current regulation are highlighted.